EPID-20. TRENDS IN GLIOBLASTOMA OUTCOMES OVER TIME, GEOGRAPHIC LOCATION AND TYPE OF INTERVENTION. (11th November 2019) - Marenco-Hillembrand, Lina; Wijesekera, Olindi; Suarez-Meade, Paola; Mampre, David; Jackson, Christina; Ortiz, Kyle; Lesser, Elizabeth; Hawayek, Maria; Vivas-Buitrago, Tito; Quinones-Hinojosa, Alfredo; Chaichana, Kaisorn
Abstract: INTRODUCTION: The management of glioblastoma (GBM) has changed over time and varies based on geographic location. Despite its universally fatal prognoses, it is unclear if GBM outcomes have changed over time, if they vary by geographic location, and differ based on type of intervention. As a result, we conducted a systematic review of the literature to identify the average survival differences of GBM patients across time, between different continents, and among various treatments. METHODS: The systematic review of PubMed included glioblastoma, GBM, and survival. Inclusion criteria consisted of full-text titles with human subjects, GBM/Grade IV astrocytoma, age >18 years old, and with available survival data. RESULTS: 9, 162 articles were screened for survival data, 1728 were eligible, 405 complied with the inclusion criteria. Of the 405 studies, 179 (44.2%) were conducted in Europe, 151 (37.3%) in the Americas, 61 (15.1%) in Asia, 9 (2.2%) in Oceania, and 1 (0.2%) in Africa. Leading countries are the United States (33.1%), Germany (12.3%), and Italy (11.1%). Asia had the highest median survival (14.9 months), followed by Europe (13.2 months), and the United States (12.9 months) (P=0.003). Regarding treatment, survival was significantly higher after the introduction of the Stupp protocol (P< 0.001). Post-Stupp Studies had longer survival estimates (15.3 months, range: 3.8–29.6) than Pre-Stupp Studies (12.2 months, range: 2.3–28). In the included clinical trials (182), radiation (43.4%), temozolomide (25.3%), or other chemotherapies (24.2%) were the most common interventions. Clinical trial median survival estimates were significantly higher than all other studies (P< 0.017). Bevacizumab (19.3 months) and Temozolomide (15.9 months) had the longest recorded median survival estimates; while radiation (14 months), other chemotherapies, and carmustine (13.2 months) had the shortest (P=0.009). CONCLUSION: This epidemiological study describes the current global state of GBM. Important differences regarding survival and treatment of patients with GBM were found.